Envy, Politics, and Age - Harris, Christine R.; Henniger, Nicole E. (Frontiers in Psychology, 2013)
In the last 5 years, the phrase “politics of envy” has appeared more than 621 times in English-language newspapers, generally in opinion essays contending that political liberalism reflects and exploits feelings of envy. Oddly, this assertion has not been tested empirically. We did so with a large adult sample (n = 357). Participants completed a Dispositional Envy Scale and questions about political ideology, socioeconomic status, and age. Envy and age were moderately correlated; younger people reported greater envy. Political ideology and envy were weakly correlated; however, this relationship was not significant when controlling for age.